2011
DOI: 10.1007/s12666-011-0052-2
|View full text |Cite
|
Sign up to set email alerts
|

Friction welding of Cu-tube to Al-tube plate using an external tool

Abstract: In the present study, friction welding of tube to tube plate using an external tool (FWTPET) was used to weld copper tubes with aluminum plates. Tubes were prepared with holes along the faying surfaces of tubes and cleaned before welding. The weld microstructure shows line of stir zone (SZ), a narrow thermo mechanically affected zone and heat affected zone (HAZ). The welded samples were found to have satisfactory joint strength and the XRD study showed the presence of AlCu intermetallic in the weld zone. The h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Advances in Civil Engineering between 1,400 and 1,900 kg/m 3 as specified by the code ASTM C 330 [44] and ASTM C 567 [45][46][47][48][49][50][51][52][53][54].…”
Section: Unit Weight Of Scc Mixesmentioning
confidence: 99%
“…Advances in Civil Engineering between 1,400 and 1,900 kg/m 3 as specified by the code ASTM C 330 [44] and ASTM C 567 [45][46][47][48][49][50][51][52][53][54].…”
Section: Unit Weight Of Scc Mixesmentioning
confidence: 99%
“…The main advantages of FW are its capability to join non-weldable material alloys to create high-grade welds, low cost and improved joint strength. This process involves a machine with suitable modifications that translate mechanical energy into heat energy without the application of electrical power that is used to weld using relative movement between workpieces [3]. FWTPET [4] of asymmetrical shape becomes a breakthrough in the year 2006.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that, the significance of FWTPET process by using different optimization techniques [7]. He also investigated the most influencing parameters both input and output by the Artificial Neural Network (ANN) and Genetic Algorithm (GA) [3]. The finite element analysis study carried out, to define the stress, strain distribution [4].…”
Section: Introductionmentioning
confidence: 99%
“…The improvement of the FWTPET process such as different tube diameter, tube preparation has been presented by Kumaran et al [11,12]. The Cu tube to Al tube plate has been used to weld satisfactory joint strength for FWTPET process by Kumaran et al [13]. The environment effect on global warming has been forcing the manufacturing process to be eco-friendly so as to deliver the product with lesser impact on the environment, energy consumption and other resource consumption.…”
Section: Introductionmentioning
confidence: 99%